Peran Organisasi Kepemudaan Dalam Meningkatkan Pemahaman Wawasan Nusantara Di Kalangan Pemuda Indonesia - Inggar Saputra (Civic-Culture : Jurnal Ilmu Pendidikan PKN dan Sosial Budaya, 2018)
This study aims to see how far the role of youth organizations in improving theunderstanding of the insight of the archipelago among young Indonesians. Thisbackground of the archipelago insight is an important and strategic conception thatmust be understood, lived and practiced by Indonesian youth. As is known, the youthorganization in Indonesia is very much, so that number must be optimized in order tobe able to immerse the understanding, appreciation, and practice of archipelagoinsight to form a strong and strong Indonesian youth. This research uses qualitativedescriptive research method. The present and future youth organizations are expectedto continue to contribute actively to enhance young people on the concept of insightinto the archipelago through implementation in the field of political, economic, social,defense and security. If it is capable, the Indonesian nation will be able to achieve itsnational goals, goals, and vision as mandated by the founders of the nation.